Empowering leadership questionnaire: Brazilian adaptation and validation - Lott, Ana Cristina de Oliveira (2023)
Purpose The present study aims to present the adaptation and validation of the empowering leadership questionnaire (ELQ) for a sample of Brazilian workers (N = 827). Design/methodology/approach The procedures of items translation, adaptation and back-translation of the original instrument were carried out. Data collection was performed using the snowball method. Data were evaluated with confirmatory factor analysis. Findings The results showed that the factor structure was maintained as in the portuguese (from Portugal) and English versions (original). Convergent validity was tested using the ethical leadership at work questionnaire (ELW). The analyses showed that the measure has good psychometric qualities, reliability indices and convergent validity results with the ELW. Research limitations/implications The ELQ can still be used to identify the presence of empowering leadership (diagnostic phase) and contribute to proposing organizational interventions that lead to healthier and more productive work environments. Its convergent validity with ethical leadership suggests that managers can apply both (empowering and ethical leadership complementarily) to create quality interactions between leaders and team members that increase workers’ autonomy and allow them to respond promptly to organizational challenges. Originality/value Using the ELQ can represent an important tool for the theoretical and practical development of studies of empowering leadership with Brazilian samples.